1996
DOI: 10.1177/026765919601100505
|View full text |Cite
|
Sign up to set email alerts
|

Platelet activation and degradation in an experimental extracorporeal system. A comparison between a silicone membrane and a hollow-fibre oxygenator

Abstract: Blood platelets are rapidly activated in contact with biomaterials and, therefore, can be used as markers of the biocompatibility of various components in an extracorporeal system. In the present work two different oxygenators, one membrane oxygenator (Avecor) and one hollow-fibre oxygenator ("Lilliput', Dideco) were compared. Complete in vitro extracorporeal membrane oxygenation circuits were perfused with fresh, heparinized human blood for 24 h. Eight experiments were performed with the hollow-fibre oxygenat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…This decline in platelet count can be explained by adherence of platelets to the artificial surfaces of the extracorporeal circuit. In previous studies reported by us and by other groups, reduced platelet consumption during in vitro extracorporeal circulation with NO was observed (1). Also, during cardiopulmonary bypass in pigs, where NO was added to the oxygenator sweep gas, a similar effect has been reported (2).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…This decline in platelet count can be explained by adherence of platelets to the artificial surfaces of the extracorporeal circuit. In previous studies reported by us and by other groups, reduced platelet consumption during in vitro extracorporeal circulation with NO was observed (1). Also, during cardiopulmonary bypass in pigs, where NO was added to the oxygenator sweep gas, a similar effect has been reported (2).…”
Section: Discussionsupporting
confidence: 66%
“…In a previous study, our group observed that nitric oxide (NO), added to the oxygenator sweep gas in an in vitro extracorporeal circulation system, prevented platelet activation and consumption (1). NO has also been added to the oxygenator sweep gas in pigs undergoing cardiopulmonary bypass, in order to reduce platelet consumption (2).…”
Section: Extracorporeal Membrane Oxygenation (Ecmo)mentioning
confidence: 99%
“…To the best of our knowledge, despite the abundance of studies that quantitatively assessed the effect of platelet activation (i.e., thrombus formation) in ECC components (Mellgren et al 1996;Tanaka et al 2001), there are no studies that quantitatively assessed the mechanical factors initiating platelet activation in ECC membrane oxygenators. Gartner et al (2000) demonstrated that low velocity regions qualitatively matched regions with a high incidence of thrombotic deposition.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that hemolysis occurs while on CPB. In a comparative study of biocompatibility between a membrane and hollow fiber oxygenator, Mellgren et al (12) evaluated free hemoglobin levels in plasma at 60 ± 10 mg/dl and 310 ± 80 mg/dl in both groups after a 24 hr investigation period. The values measured in our study were 43 ± 30 mg/dl in the DBT group and 28 ± 6.6 mg/dl in the control group after a 3 hr recirculation period.…”
Section: Discussionmentioning
confidence: 99%